2021
DOI: 10.1051/0004-6361/202141160
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of environmental tracers and consequences for determining the Type Ia supernova magnitude step

Abstract: Type Ia Supernovae (SNe Ia) are standardizable candles that allow us to measure the recent expansion rate of the Universe. Due to uncertainties in progenitor physics, potential astrophysical dependencies may bias cosmological measurements if not properly accounted for. The dependency of the intrinsic luminosity of SNe Ia with their host-galaxy environment is often used to standardize SNe Ia luminosity and is commonly parameterized as a step function. This functional form implicitly assumes two-populations of S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Kelly et al 2010). Magnitude steps versus other host galaxy properties -particularly (local) specific star formation rate (Lampeitl et al 2010;Rigault et al 2013Rigault et al , 2015Rigault et al , 2020Jones et al 2018;Kim et al 2018;Briday et al 2022) -have also been observed. Although empirically well studied in the optical, the possibility of a NIR mass step has only been investigated in a small number of recent works (Ponder et al 2021;Uddin et al 2020;Johansson et al 2021;Jones et al 2022).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Kelly et al 2010). Magnitude steps versus other host galaxy properties -particularly (local) specific star formation rate (Lampeitl et al 2010;Rigault et al 2013Rigault et al , 2015Rigault et al , 2020Jones et al 2018;Kim et al 2018;Briday et al 2022) -have also been observed. Although empirically well studied in the optical, the possibility of a NIR mass step has only been investigated in a small number of recent works (Ponder et al 2021;Uddin et al 2020;Johansson et al 2021;Jones et al 2022).…”
Section: Introductionmentioning
confidence: 84%
“…The interpretation of the mass as a tracer of intrinsic SN Ia properties has recently been supported by Briday et al (2022), in their analysis of 110 low redshift SNe Ia observed by the Nearby Supernova Factory (SNfactory; Aldering et al 2002Aldering et al , 2020Rigault et al 2020). They found that the data were well modelled as coming from two underlying populations, best traced by local specific star formation rate (lsSFR) or total host galaxy stellar mass, and differing in post-standardization magnitude by 0.12 mag.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other tracers, like host galaxy stellar mass (Kelly et al 2010;Sullivan et al 2010;Childress et al 2013;Betoule et al 2014) or just host morphology (Pruzhinskaya et al 2020), are finding the same correlation between SN Ia luminosity and their environment. Recently, Briday et al (2022) have shown that all these tracers are compatible with two SN Ia populations differing in standardized magnitude by at least 0.12 ± 0.01 mag.…”
Section: Introductionmentioning
confidence: 87%
“…A similar step in peak brightness is also observed when considering other host galaxy properties, such as specific star-formation rate (sSFR; Sullivan et al 2010;Rigault et al 2020), gas phase metallicity (Gallagher et al 2005;Childress et al 2013), rest-frame galaxy colour (Roman et al 2018;Kelsey et al 2021), and emission line equivalent widths (Dixon et al 2022). By assuming that the step is caused by two populations of SNe Ia that can be (imperfectly) probed by one of these environmental tracers, Briday et al (2022) showed that the size of the step is correlated with the level of population contamination across the step location of the given host galaxy tracer, with spectroscopically observed local sSFR and global stellar mass displaying the least contamination and largest steps. One interpretation of local sSFR being the best step tracer is that SNe Ia of different ages have different standardised luminosities, perhaps representing two (or more) SN Ia populations.…”
Section: Introductionmentioning
confidence: 99%